Navigating Treatment Dilemmas: Exploration of Strategies in Managing Unfavorably Positioned Maxillary Impacted Canines with Contraindication to Traction - Unmasking Orthodontic Perspectives - Gargi Singh; Purva Joneja; Tanveer Akhtar; Oshin Pawar; Mahathi Gurijala; Rani Mehrotra (Indian Journal of Dental Sciences)
Context: Maxillary impacted canines, particularly those that are unfavorably positioned, present significant challenges in orthodontic treatment. While orthodontic traction is often considered the standard approach, there are instances where it is deemed inadvisable; management of such cases requires a multidisciplinary approach involving careful diagnosis, treatment planning, and execution. Aim: The purpose of this study is to evaluate the preferred diagnostic measures, strategies, their efficacy, and complications that may arise in managing an unfavorably positioned maxillary impacted canine when conventional orthodontic traction is deemed inadvisable, as determined by orthodontic professionals and its conversance with the current body of knowledge. Settings and Design: The study design involves an online cross-sectional questionnaire survey. Subjects and Methods: A structured questionnaire incorporating questions about preferred diagnostic criteria, alternative management approaches, and perceived challenges in managing unfavorably positioned maxillary impacted canines where orthodontic traction is contraindicated; was circulated using Google Form through professional forums and online platforms over a 4-week period. The respondents were orthodontic professionals pan India, which selected using a convenience sampling technique to ensure a representative sample. Statistical Analysis Used: One hundred responses were obtained from the participating orthodontic professionals. Data collected via google form were entered in excel and analysed using descriptive and frequency statistics in SPSS (version 23). A Chi-square test was used to find association. Results: About 70% of respondents used all available diagnostic tools (Panoramic X-ray, CBCT, IOPA). About 75% of respondents identified individuals over 18 years as the most unfavorable age group for orthodontic traction. About 75% of participants indicated that a cusp tip above the apical third of the adjacent incisor is unfavorable. About 80% considered canines completely overlapping the lateral incisor as unfavorable. About 85% identified an angulation over 45° to the midline as unfavorable. Palatal impaction was deemed most unfavorable by 55%. Most recommended alternate treatment approach for impacted canine which are contraindicated for traction was retention of impacted canine in situ (55%). Pertaining to the knowledge, attitudes, and practices of orthodontic professionals regarding the management of unfavorably positioned maxillary impacted canines and its conversance with the current body of knowledge; there is a statistically significant association. Conclusion: By carefully assessing the anatomical position, angulation and considering patient-related factors, as well as through a comprehensive understanding of potential risks and benefits of each option dental professionals can make informed decisions regarding most appropriate treatment modality and can guide patients toward optimal esthetic and functional outcomes, restoring harmony and function to their smiles.